Efektifitas Campuran Bahan Bakar Pertalite dan Zat Aditif terhadap Performa Mesin Kendaraan - Oki Prasetyo Putro; Rizqi Fitri Naryanto (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
This study aims to analyze the effectiveness of a mixture of Pertalite fuel and additives on vehicle engine performance. The method used was a systematic review with a quantitative approach of various relevant previous studies. Data were collected from national and international journals published between 2015 and 2025. The literature selection process was conducted using the PRISMA method, resulting in 12 articles meeting the inclusion criteria. The analysis results show that adding additives to Pertalite fuel can increase engine power by 3%-10% and torque by 2%-8%. Furthermore, fuel consumption decreased by 3%-8%, indicating improved combustion efficiency. Exhaust emissions, particularly carbon monoxide (CO) and hydrocarbons (HC), also decreased significantly. It was concluded that the use of additives in Pertalite has a positive impact on engine performance, although its effectiveness is influenced by the type of additive, mixture composition, and engine condition.